An Investigation of Online Peer Feedback in Improving Students’ English Writing Skills during Covid-19 Pandemic in Southern Border Provinces, Yala Rajabhat University, Thailand - คุ่ยยกสุย สิริกานต์ (วารสารศึกษาศาสตร์ มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2024)
The purpose of the study was to look into how online peer feedback affected students’ English writing skills in L2 writing classes. A writing pretest, posttest, and self-written reflection were used in the experiment as part of a mixed-methods study using an integrated experimental design. A dependent simple t-test was used to assess the data quantitatively, while content was thematically analyzed for the qualitative data. The subjects were 46 undergraduate students majoring in English in the three southernmost border provinces of Thailand. The results showed that the students had improved significantly in their writing skills based on the mean scores of the pretest and post-test. Students also noted that receiving online peer feedback helped them understand the writing process, develop affective strategies, support their critical thinking abilities, and grow socially and intellectually through teamwork. Online peer feedback was seen as a valuable experience for social interaction by students. Additionally, it gave them practice in becoming more independent learners. Online peer feedback should therefore be used in L2 writing classes.